2018
DOI: 10.14429/dlsj.3.12907
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure and Nutritional Status of Sailors During One Month of Extensive Physical Training

Abstract: The present study was conducted to determine nutritional requirements during extensive physical training by sailors of Indian Navy. A total of 37 sailors who were undergoing physical trainers course at training establishment of Indian Navy participated in this study. Energy expenditure, energy intakes, nutrient status and body composition changes during one month of training were recorded. Mean energy expenditure was found to be 4035 kcal/day ± 733 kcal/day and an average intake of 4478 kcal/day ± 340 kcal/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The black trend line is the best linear fit accounting for multiple measures within studies; it is dashed to indicate non‐significance ( P = 0.15). References to these data are: (Ainslie et al., 2002; Beals et al., 2019; Bircher et al., 2006; Bourrilhon et al., 2009; Castellani et al., 2006; Clemente‐Suárez, 2015; Coker et al., 2018; Costa et al, 2014; Diaz et al., 1991; Ebine et al., 2002; Edwards et al., 1993; Forbes‐Ewen et al., 1989; Frykman et al., 2003; Fudge et al., 2006; Geesmann et al., 2014; Glace et al., 2002; Hill and Davies, 2001; Hoyt et al., 1991; Hoyt et al., 1994; Hulton et al., 2010; Johnson et al., 2017; Jones et al., 1993; Knechtle et al., 2010; Knechtle et al., 2011; Koehler et al., 2011; Margolis et al., 2013; Margolis et al., 2016; Mudambo et al., 1997; Mullie et al., 2018; Plasqui et al., 2019; Pulfrey and Jones, 1996; Rehrer et al., 2010; Reynolds et al., 1999; Ryder et al, 2004; Schulz et al., 1992; Sjodin et al., 1994; Stroud, 1998; Stroud et al., 1993; Stroud et al., 1997; Verma et al., 2018; Westerterp et al., 1986; Westerterp et al., 1992; Westerterp et al., 1994)…”
Section: Discussionmentioning
confidence: 99%
“…The black trend line is the best linear fit accounting for multiple measures within studies; it is dashed to indicate non‐significance ( P = 0.15). References to these data are: (Ainslie et al., 2002; Beals et al., 2019; Bircher et al., 2006; Bourrilhon et al., 2009; Castellani et al., 2006; Clemente‐Suárez, 2015; Coker et al., 2018; Costa et al, 2014; Diaz et al., 1991; Ebine et al., 2002; Edwards et al., 1993; Forbes‐Ewen et al., 1989; Frykman et al., 2003; Fudge et al., 2006; Geesmann et al., 2014; Glace et al., 2002; Hill and Davies, 2001; Hoyt et al., 1991; Hoyt et al., 1994; Hulton et al., 2010; Johnson et al., 2017; Jones et al., 1993; Knechtle et al., 2010; Knechtle et al., 2011; Koehler et al., 2011; Margolis et al., 2013; Margolis et al., 2016; Mudambo et al., 1997; Mullie et al., 2018; Plasqui et al., 2019; Pulfrey and Jones, 1996; Rehrer et al., 2010; Reynolds et al., 1999; Ryder et al, 2004; Schulz et al., 1992; Sjodin et al., 1994; Stroud, 1998; Stroud et al., 1993; Stroud et al., 1997; Verma et al., 2018; Westerterp et al., 1986; Westerterp et al., 1992; Westerterp et al., 1994)…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that during short-duration, high-intensity physical training, carnosine can act as a buffer on the increase of H + ions. This is one of the main reasons why it is used as an ergogenic supplement, especially in vegetarian athletes who have lower muscle carnosine levels than omnivorous athletes [54,55]. Also to be considered is the use of dietary supplements such as energy bars (fruit bars, granola bars, protein bars, fibrous bars, etc.…”
Section: Nutrition and Supplements For Hikersmentioning
confidence: 99%